Relationship between gender-based violence involving a partner and social support among Colombian women: analysis from a gender perspective - Reina-Barreto, Johanna Alexandra (Cuadernos de Trabajo Social, 2021)
This study compares the sociodemographic and socioeconomic characteristics, types, intensities and consequences of violence in a group of adult women seeking social support due to having suffered violence from a (former) heterosexual partner in relation to a group of women who have not sought support. It describes the sources of support that make up formal and informal networks, their density, and the relationship between seeking support and the violence experienced. The sample was made up of 6,279 women aged between 25 and 49 years who responded to the Bogota-2011 Health Survey (Encuesta de salud Bogotá-2011). Contingency tables were used with a Chi-squared contrast and Cramér’s V coefficient in order to confirm the intensity of the relationship between variables. The findings show a high prevalence of violence across all categories studied; women who sought support reported up to three times more violence and consequences than the women in the sample who did not seek it. Those who did not seek support lives with their abuser in families with patriarchal characteristics and with potential family witnesses to the violence. Those who sought support were separated or divorced with more children, with a family as their main source of support, although the structure of the network changes as more violence accumulates. The overall findings suggest a continuum of violence, where control operates as a culturally legitimated system of oppression. It is proposed that these results could usefully be applied when designing programmes for interventions with women.